A minimally invasive bipolar surgical approach for the treatment of patellar fracture using the tension-band wiring technique - Lin, Zhangxiong; Chen, Yaoqing; Wang, Hai; Lan, Wenbin; Xie, Yun; Wu, Gui (Frontiers in Surgery, 2022)
Objective: Minimally invasive surgical techniques are being increasingly popular for the treatment of traumatic injuries. Although some minimally invasive techniques in the management of patellar fractures have been reported, the limited exposure may result in technical difficulty of surgery and restrict the wide application. The objective for this study is to introduce a bipolar incision and to assess the clinical outcomes of patellar fractures treated via the bipolar incision. Materials and Methods: Patients who have patellar fracture and receive surgical treatment via the bipolar incision between 2018 and 2020 in our hospital were retrospectively reviewed and included in this study. Clinical and radiological records were reviewed for all patients. Classification of the fractures, intraoperative parameters, Visual Analogue Scale (VAS) score, knee range of motion and the Hospital for Special Surgery (HSS) knee score of the patients were evaluated and summarized. Results: A total of 19 patients met the inclusion criteria and was studied. All of patellar fractures were operated through the minimally invasive bipolar surgical approach. The mean time of operation was 69.0±8.5 min. The mean time to union was 12.8±2.1 weeks. The average total knee range of motion was 131.8±4.4°, and the average HSS score was 97.1±2.6 at 1-year post operation. No surgical related complications were observed. Conclusions: The knee functional outcomes were favorable when patellar fractures were treated through the minimally invasive bipolar incision. Minimally invasive bipolar surgical approach was a feasible method for patellar fracture.